Impact of casein glycomacropeptide on sodium caseinate self-assembly and gelation - Morales, Rocio (2015)
The effect of casein glycomacropeptide (CMP) on the self-assembly and gelation of sodium caseinate (NaCas) was studied. Acid gelation was induced by the addition of glucono-δ-lactone to NaCas alone and to NaCas/CMP mixtures at ratios 1/1 and 3/1. The results showed that the interactions among NaCas and CMP, determined by particle size measurement, affect the self-assembly of NaCas that occurs on decreasing pH. When the decrease in pH leads to the formation of NaCas acid gels, the presence of CMP alters the pH of gelation, texture and microstructure of these gels, resulting in a protein network with smaller aggregates and higher strength. Therefore, the incorporation of CMP on NaCas solutions not only has a potential benefit related to the bioactive properties provided by CMP, but also provides a control in the textural properties of the gels obtained by acidification.